Design and fabrication of ultrasonic tomographic instrumentation system for inspecting flaw on pipeline - Nordin, Norsuhadat (2015)
Pipeline inspection is a key factor in the pipeline maintenance process to optimize the pipe condition. It is important to detect and to locate the flaw or defect before it grows into a critical size that may fail the pipeline's operation, which could lead to severe damage such as explosion and fatal incident. An accurate and reliable data on flaws or defects are compulsory to assess the pipe condition. Hence, a non-intrusive tool can be used for the pipe inspection, which is an ultrasonic tomography instrumentation system. Modelling and designing the instrumentation has been done thoroughly prior to the fabrication the system. There are 28 of ultrasonic transceiver sensors mounted on the ultrasonic sensing ring, with 50 mm distance to the pipe surface. The image area of ultrasonic signal produced by each sensor is 20 mm. The average accuracy of distance calibration is about 99.82% for a sensing range of 40 to 60 mm from the sensor to the pipe surface. An image of the pipe with flaws existence is reconstructed based on the data obtained from the experimental work.